1991
DOI: 10.1113/jphysiol.1991.sp018748
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of long‐term denervated rat soleus muscle and the effect of chronic electrical stimulation.

Abstract: SUMMARY1. Rat soleus muscles were denervated for 6-10 months; some of these were chronically stimulated for the last 3-8 weeks before recording. The muscles were fixed at physiological lengths and embedded in epoxy resin.2. Sections for light microscopy were stained with p-phenylenediamine. Denervation reduced the mean cross-sectional area of fibres to 3% of controls (peak at 20 ,tm2). The cross-sectional areas of the stimulated fibres had a peak at 70 ,um2. In light micrographs of denervated muscles, the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 17 publications
6
109
0
Order By: Relevance
“…We attempted a light microscopical study of these muscles (Al-Amood & Lewis, 1989a) which suggested that loss of fibres could be prevented by stimulation. A more detailed ultrastructural examination, which is reported in the preceding paper, (Schmalbruch, Al-Amood & Lewis, 1991) showed, however, that the effects of electrical stimulation on degeneration and necrosis are more complicated than suggested by our preliminary histology.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…We attempted a light microscopical study of these muscles (Al-Amood & Lewis, 1989a) which suggested that loss of fibres could be prevented by stimulation. A more detailed ultrastructural examination, which is reported in the preceding paper, (Schmalbruch, Al-Amood & Lewis, 1991) showed, however, that the effects of electrical stimulation on degeneration and necrosis are more complicated than suggested by our preliminary histology.…”
Section: Introductionmentioning
confidence: 85%
“…It is possible to use the changes in tension following denervation and stimulation with the morphological data (light microscopy in 3 ,um epoxy sections: Schmalbruch et al 1991) to calculate the specific tension (force per unit cross-sectional area), and the results are set out in Table 3. As would be expected, there was a large (70-fold) reduction in mean fibre size in denervated soleus and this was accompanied by an 8-fold fall in specific tension.…”
Section: Tension and Fibre Sizementioning
confidence: 99%
“…16 Electrical stimulation has been shown to improve muscle ®ber structure and function. 15,17,18 In animal models, investigators have reported the deleterious e ect of denervation on postreceptor insulin action, 19 exercise-induced glucose uptake, 20 insulin receptor binding, 21,22 receptor phosphorylation, 21 and the glucose transporter protein (GLUT-4). 23 ± 25 In a recent study, 26 individuals with tetraplegia were found to have a marked reduction in whole body glucose transport that appeared to be due to a proportional reduction in muscle mass.…”
Section: Determinants Of Insulin Resistancementioning
confidence: 99%
“…4,6,23 These newly formed fibers, thoroughly characterized at the ultrastructural level, contain a poorly developed contractile system with many degenerated elements. 4 These incompletely differentiated fibers appear to arise from satellite cells that have detached from their parent myofibers, representing an "abortive" attempt at myogenesis.…”
mentioning
confidence: 99%
“…4 Schmalbruch and colleagues described similar myofibers in rat muscle denervated for 6 -10 months. 23 As small as 1 m in diameter, the majority of these muscle cells were so small that they could not be identified by routine light microscopy. Schmalbruch and colleagues further noted that some of the smaller fibers were completely devoid of myofilaments.…”
mentioning
confidence: 99%